1995
DOI: 10.1111/j.1365-2648.1995.tb02724.x
|View full text |Cite
|
Sign up to set email alerts
|

Heparin and haematoma: does ice make a difference?

Abstract: Subcutaneous heparin injections are frequently prescribed for the prevention of deep vein thrombosis. One of the most commonly encountered adverse physiological responses to this intervention is the formation of a haematoma at the injection site. This creates a challenge for the nurse attempting to minimize haematoma formation and/or patient discomfort during the treatment regime. The purpose of this study was to determine if the application of ice to subcutaneous heparin injection sites decreases the incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 10 publications
0
38
1
6
Order By: Relevance
“…They showed a significant difference between the heparin injection methods by applying cold packs versus injection methods with no cold pack application. However, the studies by Kuzu & Ucar (2001) and Ross & Soltes (1995) showed no statistically significant difference between incidence of bruising and applying of local cold packs on the injection site. Perhaps, the most important reasons for these controversial results can be the differences in duration of cold pack applications, temperature of cold packs and/or research designs.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…They showed a significant difference between the heparin injection methods by applying cold packs versus injection methods with no cold pack application. However, the studies by Kuzu & Ucar (2001) and Ross & Soltes (1995) showed no statistically significant difference between incidence of bruising and applying of local cold packs on the injection site. Perhaps, the most important reasons for these controversial results can be the differences in duration of cold pack applications, temperature of cold packs and/or research designs.…”
Section: Discussionmentioning
confidence: 98%
“…However, other researchers (Kuzu & Ucar, 2001;Ross & Soltes, 1995) identified that cold application had no statistically significant impact on the incidence or size of a hematoma at heparin injection sites. Kuzu & Ucar (2001) studied the effect of cold on the occurrence of hematomas and bruising at the subcutaneous enoxaparin injection sites in three intervention groups (five minute pre-injection application of ice, five minute post-injection application of ice, five minute pre and post application of ice) and a control group (no application of ice).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been stated that cold treatment over the area where surgical sutures are found after lumbar disc surgery reduces both the pain during first 24 hours and the need for morphine (Brandner et al 1996). Also, it has been shown that fluoromethane spray applications are a cheap method that are rapidly effective in managing the injection pain due to vaccination (Mawhorter et al 2004) and cold package and ice applications have reduced the pain due to heparin injections (Kuzu ve Uçar 2001;Ross and Soltes 1995). In the study that they conducted, Demir and Khorshid (2010) have stated that cold treatment that is applied to the skin around the chest tube reduced the severity of the pain that is felt due to exclusion of chest tube and it has extended the time between exclusion of chest tube and taking an analgesic.…”
Section: Tens (Transcutaneous Electrical Nerve Stimulation)mentioning
confidence: 99%
“…Research affirms that the administration technique the nursing professional uses can influence the occurrence of these events and the pain intensity levels [5,10,11] . Factors like the injection site, size of needle, amount of heparin, applying, aspiration before the injection, post-injection massage and duration of injection can influence the occurrence of bruising [6] .…”
Section: Introductionmentioning
confidence: 99%